Pengaruh Kredit Pertanian Terhadap Kesejahteraan Petani di Indonesia: The Effect of Agricultural Credit on Farmers Welfare in Indonesia - Rozci, Fatchur; Laily, Dona Wahyuning (Jurnal Ilmiah Manajemen Agribisnis, 2023)
Agriculture is an important sector in a country's economy because it makes a major contribution to the Gross Domestic Product (GDP) in Indonesia. According to data from the Central Statistics Agency (BPS) for 2021 the agricultural sector contributed 13.70% to GDP. Farmers in Indonesia are mostly located in rural areas and have less access, so the government must provide support such as providing capital by making agricultural credit policies to support the sustainability of agricultural businesses and improve the welfare of farmers. The agricultural credit policy is one of the government's efforts to facilitate farmers' access to capital to develop their agricultural businesses. This research 'The Influence of Agricultural Credit on the Welfare of Farmers in Indonesia' uses a literature review approach by collecting data or sources related to a particular topic from various sources, such as journals, books, the internet and other library sources. The results of this summary, analysis, and synthesis are then written descriptively in the form of scientific articles. The Influence of Agricultural Credit on Farmer Welfare in Indonesia aims to determine agricultural credit policies, farmer welfare, the application of agricultural credit and the influence of agricultural credit.